2018
DOI: 10.1093/ndt/gfy189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erythropoietin on fibroblast growth factor 23 in mice and humans

Abstract: EPO affects FGF23 production and metabolism, which may have important implications for CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 49 publications
9
96
0
Order By: Relevance
“…A direct relationship between EPO and FGF23 has been shown as concentration of FGF23 increases after injection of recombinant human (rh) EPO in mice/rats as well as in humans. (16,17,38,39) In a murine model with chronically elevated EPO and normal renal function, similar results have been noted with positive association between EPO and serum levels of FGF23. (39) Furthermore, when injecting mice with FGF23, a decreased renal EPO mRNA has been noted, suggesting a negative feedback loop between EPO and FGF23.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A direct relationship between EPO and FGF23 has been shown as concentration of FGF23 increases after injection of recombinant human (rh) EPO in mice/rats as well as in humans. (16,17,38,39) In a murine model with chronically elevated EPO and normal renal function, similar results have been noted with positive association between EPO and serum levels of FGF23. (39) Furthermore, when injecting mice with FGF23, a decreased renal EPO mRNA has been noted, suggesting a negative feedback loop between EPO and FGF23.…”
Section: Discussionsupporting
confidence: 73%
“…(16,17,38,39) In a murine model with chronically elevated EPO and normal renal function, similar results have been noted with positive association between EPO and serum levels of FGF23. (39) Furthermore, when injecting mice with FGF23, a decreased renal EPO mRNA has been noted, suggesting a negative feedback loop between EPO and FGF23. (17) Effort was made adjusting for levels of FGF23 when assessing EPO's effect on fracture risk.…”
Section: Discussionsupporting
confidence: 73%
“…WT mice given acute rhEPO treatment after 6 h or after 3–4 days of consecutive injections resulted in elevated total and intact FGF23 and bone marrow Fgf23 mRNA expression ( 64 ). To understand the effects of chronically elevated EPO, reports using the transgenic Tg6 mouse model of EPO overexpression showed that these mice have basal elevations in total and intact FGF23 ( 65 , 67 ). Chronic overexpression of EPO can lead to iron deficiency, so to determine whether the iron deficiency was causing the elevated FGF23, mice were given iron dextran.…”
Section: Fgf23 Production and Cleavage In Osteocytesmentioning
confidence: 99%
“…Regulators of FGF23 production in bone include 1,25(OH) 2 D 3 , PTH, inflammation, the iron status, erythropoietin, intracellular posttranslational regulators (GalNAc‐T and FAM20c; ) as well as intracellular signaling pathways (eg, AMP‐dependent signaling or phosphoinositide 3‐kinase (PI3K) signaling). FGF23‐expressing UMR106 osteoblast‐like cells express both, endothelin A (ETA) and endothelin B receptors (ETB)…”
Section: Introductionmentioning
confidence: 99%